Trabectedin is a promising antitumor agent potentially inducing melanocytic differentiation for clear cell sarcoma. (26th July 2017) - Nakai, Takaaki; Imura, Yoshinori; Tamiya, Hironari; Yamada, Shutaro; Nakai, Sho; Yasuda, Naohiro; Kaneko, Keiko; Outani, Hidetatsu; Takenaka, Satoshi; Hamada, Kenichiro; Myoui, Akira; Araki, Nobuhito; et al.
Abstract: Clear cell sarcoma is an aggressive soft tissue sarcoma and highly resistant to conventional chemotherapy and radiation therapy. This devastating disease is defined by EWSR1‐ATF1 fusion gene resulting from chromosomal translocation t(12;22)(q13;q12) and characterized by melanocytic differentiation. A marine‐derived antineoplastic agent, trabectedin, inhibits the growth of myxoid liposarcoma and Ewing sarcoma by causing adipogenic differentiation and neural differentiation, respectively. In this study, we examined the antitumor effects and mechanism of action of trabectedin on human clear cell sarcoma cell lines. We showed that trabectedin decreased the cell proliferation of five clear cell sarcoma cell lines in a dose‐dependent manner in vitro and reduced tumor growth of two mouse xenograft models. Flow cytometry and immunoblot analyses in vitro and immunohistochemical analysis in vivo revealed that trabectedin‐induced G2/M cell cycle arrest and apoptosis. Furthermore, trabectedin increased the expression of melanocytic differentiation markers along with downregulation of ERK activity in vitro and the rate of melanin‐positive cells in vivo. These results suggest that trabectedin has potent antitumor activity against clear cell sarcoma cells by inducing cell cycle arrest, apoptosis, and, in part, by promoting melanocytic differentiation through inactivation of ERK signaling. Our present study indicates that trabectedin is a promising differentiation‐inducing agent for clear cell sarcoma. Abstract : Clear cell sarcoma is an aggressive soft‐tissue sarcoma and highly resistant to conventional chemotherapy and radiation therapy. Our present study suggests that trabectedin has potent antitumor activity against clear cell sarcoma cells by inducing cell cycle arrest, apoptosis, and, in part, by promoting melanocytic differentiation.